2020
DOI: 10.1088/1757-899x/942/1/012015
|View full text |Cite
|
Sign up to set email alerts
|

Re-use of wind turbine blade for construction and infrastructure applications

Abstract: To achieve a more resource-efficient society with a future with reduced carbon dioxide emissions, new technological challenges must be dealt. One way to reach a more sustainable world is to start re-using end-of-life structures and waste and give them a ‘Second Life” with a new function in the society. As composite structures are lightweight, strong, stiff and durable materials, there is great potential to re-use decommissioned composite for new resource-efficient solutions in the building and infrastructure s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Figure 5 shows an example of these structures. Other applications include bridges (which requires additional testing and special design efforts), playgrounds, bus shelters, and other urban furniture [ 70 , 82 , 83 , 84 ]. Bank et al [ 85 ] suggested to re-use parts of wind blades in new or retrofitted housing projects in Mexico, where harsh environmental conditions (water and high humidity) exist.…”
Section: Recycling Of Wind Turbine Bladementioning
confidence: 99%
“…Figure 5 shows an example of these structures. Other applications include bridges (which requires additional testing and special design efforts), playgrounds, bus shelters, and other urban furniture [ 70 , 82 , 83 , 84 ]. Bank et al [ 85 ] suggested to re-use parts of wind blades in new or retrofitted housing projects in Mexico, where harsh environmental conditions (water and high humidity) exist.…”
Section: Recycling Of Wind Turbine Bladementioning
confidence: 99%
“…Five narrative-based descriptions of demographics, human development, economy and lifestyle, policies and institutions, technology, and environment, and natural resources in the future represent potential societal developments. The scenarios are Sustainable development [48], Middle-of-the-road development [22], Regional rivalry [50], Inequality [51], and Fossil-fueled development [52] including long-term demographic and economic changes with a multimodel approach to project energy, land-use, and emissions trajectories [53]. For this study, we consider SSP1 as the best case, SSP2 as the middle of the road, and SSP5 as the worst case to have a clear picture of the future window of opportunities.…”
Section: Ssp Scenariosmentioning
confidence: 99%
“…Structural repurposing is when sections of the blade are cut to size and used directly in making new products such as furniture [21]or bridges [22]. However, this EoL strategy is difficult to scale, and with future waste volumes in mind, more large-scale technologies must be implemented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the need for environmentally responsible behavior is driving wind farm owners and turbine OEMs (original equipment manufacturer) to look for sustainable repurposing of wind blades in new structural applications (see for example www.re-wind.info (accessed on 6 July 2021)) [6][7][8]. Other small, medium, and large-scale structural reuse applications have also been described by Joustra et al [9,10], André et al [11], and Jensen and Skelton [12].…”
Section: Introductionmentioning
confidence: 99%